A REVIEW: MICROSPONGE-AN EFFECTIVE DRUG DELIVERY SYSTEM - Shrivastava, Saumya; Kumar, Deepak; Dubey, Chetan Kumar; Singh, Surya Pratap; Khinchi, M. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Microsponge Delivery System (MDS) is a unique technology for controlled delivery of drug. MDS technology has been introduced in topical drug products to facilitate the controlled release of active drug into the skin in order to reduce the systemic exposure and minimize local cutaneous reactions to active. Microsponge technology has been clinically tested with many active ingredients in full formations, providing strong product claims. Microsponge literally means a collection of very small, sponge like particles, having a large porous surface, used for drug delivery. Microsponge particles are also referred to as microsphere beads or microspheres. The chemical manufacture of Microsponge involves careful polymerization using specific inert monomers, which may be selected based on their compatibility with individual active ingredients. The method of Microsponge manufacture is dependent on the chemical characteristics and “fragility” of the active ingredient.